Review on Malahara Kalpanas Indicated in Vipadika (International Journal of Ayurveda and Pharma Research, 2025)
Malahara Kalpana can be regarded as a traditional Ayurvedic ointment preparation. Depending on the intended application, these formulations usually have a base of Siktha taila together with powdered herbal, metallic, or mineral drugs. Beeswax and Tila taila are combined in a ratio of either 1:6 or 1:5 to make Siktha taila. Vipadika is one of the skin disorders that Malahara Kalpanas are used to heal. Vipadika, often referred to as cracked feet, is a common but neglected volar skin condition. It is characterized by Darana (cracks), Kandu (itching), and Vedana (pain). Due to its properties of oleation, cleansing, healing, and scar reduction, Malahara Kalpana is beneficial for treating Vipadika. This paper aims to discuss the possible actions of Malahara preparations indicated for the treatment of Vipadika.